Agile and Innovative Leadership Paradigms in Building Organizations Responsive to Change: A Review of Rhenald Kasali's Thoughts - Sri Haryanti; Gibralta Royal Mahadiva Abdullah (UNIVED Press, 2026)
This article explores the paradigm of Agile and Innovative Leadership in building organizations that are responsive to change, with a critical examination of the thoughts of Rhenald Kasali, a prominent Indonesian management thinker and practitioner. Kasali emphasizes the crucial role of visionary leaders who possess the ability to adapt swiftly to the dynamics of a complex business environment. His works highlight the necessity for leaders to foster an organizational culture that encourages innovation, continuous learning, and agility. By applying Agile principles, leaders can create competitive and responsive teams that are well-equipped to navigate the challenges of disruption and rapid transformation. This discussion asserts that Kasali's insights are particularly relevant to the pressing needs of the nation, where enhancing literacy in change, innovation, and disruption is essential for sustainable growth and development. Ultimately, the article underscores the importance of developing forward-thinking leaders who can guide their organizations towards resilience and success in an ever-evolving landscape.